Considerations in Using US-Based Laboratory Toxicity Tables to Evaluate Laboratory Toxicities Among Healthy Malawian and Ugandan Infants - Lubega, Irene R.; Fowler, Mary Glenn; Musoke, Philippa; Elbireer, Ali; Bagenda, Danstan; Kafulafula, George; Ko, Jeanne; Mipando, Linda; Mubiru, Mike; Kumwenda, Newton; Taha, Taha; Jackson, J. Brooks; et al. (Journal of acquired immune deficiency syndromes, 1999)
Objectives—To determine normal hematologic and selected blood chemistry values among healthy, full-term, non–HIV-exposed infants in Uganda and Malawi, and to determine the proportion of healthy babies with an apparent laboratory toxicity based on Division of AIDS oxicity tables. Design—This was a cross-sectional laboratory study of infants from birth to 6 months of age. Methods—Blood samples were collected from a total of 561 infants and analyzed according to age categories similar to those in the 2004 Division of AIDS toxicity tables. Select chemistry and hematology parameters were determined and values compared with those in the toxicity tables. Results—In the first 56 days of life, there were few graded toxicities except for neutropenia in 2 of 10 (20%) Ugandan and 13 of 45 (29%) Malawian infants at birth. After 7 days, about 20% of the infants in Uganda and Malawi would have been classified as having a neutropenia whereas 47% and 53% of those more than 2 months of age in Uganda and Malawi respectively, would have been reported as having an abnormal hemoglobin. Chemistry findings were not different from US norms. Conclusions—These findings underscore the importance of establishing relevant local laboratory norms for infants.
Keywords: Division of AIDS; Normal laboratory reference values; Non–HIV-exposed; Toxicity tables; Ugandan; Malawian; Infants